Analisis Kandungan Borak pada Makanan di Sekitar UIN Sumatra Utara Kec. Medan Tuntungan - Preti Sinta Harahap (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Students are an investment in the nation and the nation's next generation. Their growth and development will be optimal depending on providing nutrition with good and correct quality, quantity. By consuming good food and snacks, it is hoped that you can contribute adequate nutrition. Students are used to eating and snacks whose main menu is meatballs, junkfoot and modern food currently on campus and around campus. However, currently many foods and drinks contain additional ingredients such as preservatives, borax and others. Thus, it is necessary to study and research the borax content as well as qualitative analysis of the meatballs sold by traders around the UINSU Tuntungan campus. This type of research uses total sampling carried out by the UPT HEALTH LABORATORY of the North Sumatra Provincial Health Service. located on Jl. Willem Iskandar Pasar V (Jl. Balai Pom) using qualitative methods. The research results showed that from 6 samples of meatballs located around the UIN campus, it was proven that they did not contain borax. Based on the results of the analysis, it can be concluded that all meatball sellers located around the UIN Medan Tuntungan Campus have good knowledge and attitudes which are important factors in avoiding contamination by toxic substances and how to manage meatballs properly without the use of preservatives, especially borax. The meatball processing method at UIN and around UIN meets the requirements of the Minister of Health of the Republic of Indonesia 2015, Number: 722/Menkes/Per/IX/2015 regarding food, so students don't need to worry.